2021
DOI: 10.1101/2021.06.11.447976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrasound mediated cellular deflection results in cellular depolarization

Abstract: Ultrasound has been used to manipulate cells in both humans and animal models. While intramembrane cavitation and lipid clustering have been suggested as likely mechanisms, they lack experimental evidence. Here we use high-speed digital holographic microscopy (to 100-kHz order) to visualize the cellular membrane dynamics. We show that neuronal and fibroblast membranes deflect about 150 nm upon ultrasound stimulation. Next, we develop a biomechanical model that predicts changes in membrane voltage after ultras… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 56 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…Among the many potential channels, transreceptor potential A1 has demonstrated a response to ultrasound at 6.91 MHz (Duque et al, 2022). The mechanism of action was thought to involve cavitation or some sort of small-scale streaming phenomenon, but it appears that membrane deformation and consequent stretching is entirely sufficient to produce the measured effects, including the threshold response that requires a minimum level of ultrasound for ion channel activation (Vasan et al, 2021;Vasan et al, 2022). This promises to produce a method to activate or silence small groups of neurons at will in a non-invasive manner.…”
Section: Sonogeneticsmentioning
confidence: 99%
“…Among the many potential channels, transreceptor potential A1 has demonstrated a response to ultrasound at 6.91 MHz (Duque et al, 2022). The mechanism of action was thought to involve cavitation or some sort of small-scale streaming phenomenon, but it appears that membrane deformation and consequent stretching is entirely sufficient to produce the measured effects, including the threshold response that requires a minimum level of ultrasound for ion channel activation (Vasan et al, 2021;Vasan et al, 2022). This promises to produce a method to activate or silence small groups of neurons at will in a non-invasive manner.…”
Section: Sonogeneticsmentioning
confidence: 99%
“…As ultrasound waves pass though tissue, cellular membranes deflect and oscillate (Figure 1B), which drives biophysical transduction mechanisms (Lee et al, 2020). Visualization of cellular membrane dynamics in neurons using high speed digital holographic microscopy shows membrane deflections occur up to 150 nm under 7 MHz ultrasound stimulation (Vasan et al, 2022). Prolonged oscillation of the membrane creates an accumulation of action potential, occurring in phase with the membrane's deflection (Heimburg and Jackson, 2005).…”
Section: Cellular Effects Of Ultrasound Neuromodulationmentioning
confidence: 99%
“…Prolonged oscillation of the membrane creates an accumulation of action potential, occurring in phase with the membrane's deflection (Heimburg and Jackson, 2005). The change in capacitance due to the elastic change in membrane area, while maintaining constant volume, induces transmembrane voltage changes and subsequent depolarization (Vasan et al, 2022). Mechanical stimuli transmitted by ultrasound transducers are then directly translated into electrical and chemical signals by membrane bound mechanosensitive receptor proteins that form gated ion channels within the lipid bilayer (Chu et al, 2022).…”
Section: Cellular Effects Of Ultrasound Neuromodulationmentioning
confidence: 99%
“…Studies have shown that the activation threshold of neuronal cell bodies in cortical grey matter is higher than that of axons in white matter (Frank & Fuortes, 1956;Nowak & Bullier, 1998). Additionally, TUS is believed to be capable of inducing depolarization via direct mechanical action (Vasan et al, 2022). It has also been observed that depolarization of axons can trigger antidromic action potentials, which then affect cortical cell bodies (Kumaravelu et al, 2018;Li et al, 2007).…”
Section: Introductionmentioning
confidence: 99%